ROS production by endogenously generated protoporphyrin ix in murine leukemia cells - Diez, B; Cordo Russo, R; Teijo, M J; Hajos, S; Batlle, A; Fukuda, H (Cellular and Molecular Biology, 2009)
Endogenous production of Protoporphyrin IX (PpIX) is successfully exploited for photodynamic therapy (PDT) on malignant cells, following 5-aminolevulinic acid (ALA) administration and light irradiation. This treatment kills cancer cells by damaging organelles and impairing metabolic pathways via cellular reactive oxygen species (ROS) generation. We studied the efficiency of PpIX synthetized from ALA on ROS generation, in the Vincristine resistant (LBR-V160), Doxorubicin resistant (LBR-D160) and sensitive (LBR-) murine leukemia cell lines. Cells were incubated 4 hr with 1 mM ALA and then irradiated during different times with fluorescent light. One hour later, production of ROS was analyzed by flow cytometry using different fluorescent probes: Hydroethidine (HE) for superoxide anion, 2’,7’ Dichlorodihydrofluorescein diacetate (DCFH-DA) for hydrogen peroxide; mitochondrial damage was examined with 3,3’ Dihexyloxacarbocyanine iodide (DiOC6). We found that superoxide anion production in the three cell lines increased with irradiation time whereas no peroxide hydrogen was detected. Mitochondrial damage also increased in an irradiation time dependent manner, being higher in the Vincristine resistant line. Previous studies have demonstrated that apoptotic cell death increased with irradiation time, which is consistent with these results, indicating that ROS are critical in ALA-PDT efficiency to kill malignant cells.